A Study of Leadership and Followership: The Case of Universiti Malaya Dental Clinic - Norzila, Mohd Haidzir (2012)
This study highlights the aspects or forces that are inherent in the subordinate position of Matrons, Receptionists and Dentists that sheds further light on the understanding of followership as it pertains to the Dental Clinic of University Malaya. The purpose of the present study was to determine the transferable or non-transferable between leadership to followership in the area of their expertise in the Dental Clinic of University Malaya environments. This study also sought to answer the following question of the respondent understanding of the terms and the acceptance of the terms of Leadership, Leader, Follower and Followership and how the respondents identify their position to the roles. Using the interview of the qualitative approach, four respondents were selected from the Dental Clinic of University Malaya area as subjects . Therefore, after a comprehensive analysis of the research findings have revealed that effective followers have leadership qualities that are similar or different from those who are placed within positions of leading and the leadership position cannot be transferred to follower as the results.